2010
DOI: 10.5020/18061230.2010.p160
|View full text |Cite
|
Sign up to set email alerts
|

Perfil comunicativo de crianças que ingressaram na educação infantil após os cinco anos de idade

Abstract: Communicative profile of children who entered in primary school after the age of five RESUMOObjetivo: Caracterizar os comportamentos comunicativos emitidos por crianças que ingressaram na Educação Infantil após os cinco anos de idade. Métodos: Tratou-se de um estudo descritivo, realizado numa cidade do interior do estado do Paraná, nos anos de 2007 e 2008, em ambientes escolar e domiciliar. Doze crianças, de ambos os gêneros, participaram do estudo, com idade variando entre 5 anos e 2 meses e 6 anos completos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Five studies were found in the theme of language and family and school environments (18,20,23,29,31) .…”
Section: Analysis Of Selected Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were found in the theme of language and family and school environments (18,20,23,29,31) .…”
Section: Analysis Of Selected Studiesmentioning
confidence: 99%
“…The only qualitative study found in this literature review (20) aimed to characterize the communicative behaviors of children whose entry in preschool occurred after the age of five. The observation of these behaviors occurred both in the school and home environments.…”
Section: Analysis Of Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations